Liminals - Blesa, Túa (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
Those that can be understood as limits of literature are presented in these pages as liminal, that is, as the boundary that separates two spaces, as a border, so they do not prevent but rather give way to the entry and exit of the literary space. Cases of the evolution of scientific texts into literature are presented and also of others from the artistic series that make literary texts their own. Against the requirement of originality of the texts, of not admitting rewriting, of intertextuality extended to pages and pages of copy or plagiarism, several texts are collected in which such a theoretical limit vanishes as such a limit and is shown as liminal.
Keywords: limit; liminal; literature-art; plagiarism; literature-science